Phenological shifts in mating and lambing timing in response to climate change in Urial wild sheep (Ovis vignei) populations in Iran - Fereshteh Khaleghdadi; Farid Salmanpour; Peyman Valizadeh; Faraham Ahmadzadeh (PLoS ONE, 2026)
Climate change is increasingly disrupting ecological processes across arid and mountainous biomes, with profound implications for the reproductive phenology of large herbivores. These species are especially climate-sensitive, as their breeding cycles are tightly coupled with vegetation dynamics driven by seasonal temperature and precipitation. Yet, in biodiversity-rich regions such as eastern Iran, where climate variability is acute and data are sparse, long-term phenological responses remain poorly understood. Here, we examine how reproductive timing in urial sheep ( Ovis vignei ), a mountain herbivore, responds to climatic variation across six protected areas, as climate-driven mismatches between birth timing and peak forage availability may reduce neonate survival and ultimately affect population viability and connectivity. Climate data (temperature, precipitation, snowfall, and humidity) from the nearest weather station to each study area, along with latitude and mean elevation of each habitat, were integrated using generalized linear mixed models (GLMMs) to assess phenological responses to environmental variables. Our results reveal clear regional differences in mating and lambing time. Mating time was significantly influenced by latitude, summer temperature, and autumn precipitation, with higher latitudes and autumn rainfall delaying mating, while warmer summers advanced it. In contrast, lambing timing was largely dictated by study area-level random effects, which accounted for the majority of variance, whereas fixed effects such as January temperature, snowfall, and latitude contributed only minimally, highlighting the dominant role of spatial differences among study areas in shaping lambing phenology. These findings, over the past decade, underscore the role of climate and latitude in shaping reproductive timing and highlight the urgent need to incorporate phenological data into adaptive wildlife management and habitat-specific climate resilience planning in vulnerable arid mountain ecosystems.